Students' Critical Thinking Skills: Analysis of fifth-grade IPAS subjects at MI Muhammadiyah 18 Sumberrejo Bojonegoro - Dwi Lailatul Khikmah; Mochammad Miftachul Huda; Ahmad Ipmawan Kharisma (Universitas Muhammadiyah Lamongan, 2025)
This study aims to analyze students' critical thinking abilities in the Natural and Social Sciences (IPAS) subjects at MI Muhammadiyah 18 Sumberrejo, Bojonegoro Regency. The background of the research is based on the low critical thinking skills of students, as seen from learning outcomes and learning processes that are still dominated by conventional methods. The study uses a qualitative descriptive method with a case study approach through data triangulation, including observations, interviews, and documentation studies of teachers and 53 fifth-grade students. The results of the study indicate that learning has not been student-centered, the use of media is less varied, and the use of technology is not yet optimal, so the five critical thinking indicators (focus, reasoning, inference, situation, and clarity) have not developed optimally. Documentation data also show that 75% of students scored below the Minimum Competency Criteria (KKM). These findings affirm the need for more interactive, contextual, and experiential IPAS learning innovations to enhance students' critical thinking skills. The research concludes that improving the quality of learning strategies is essential so that students can actively participate and develop higher-order thinking skills.